Rare metastasis of carcinoma ovary - Kamat, Amitha; Kittur, Sahaja; Hiremath, Mallikarjun G.; Dama, Swetha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
This is a case report of a 64 year old para 5 operated 2 years back for ovarian papillary adenocarcinoma presenting 2 years later with cutaneous metastases over anterior abdominal wall.